The percentage of recreational runners that might benefit from new running shoes. A likely scenario. (2nd September 2022) - Heyde, Christian; Nielsen, Anders; Roecker, Kai; Godsk Larsen, Ryan; de Zee, Mark; Kersting, Uwe; K. Brund, René B.
Abstract: Knowing how many people are likely to benefit from a newly developed running shoe is of high relevance for footwear developers, phrasing legal claims and ultimately purchasing consumers. In order to assess and evaluate a likely scenario, the between-days reproducibility of percentages benefitting from lighter conventional flat running shoes (CON) or lighter advanced shoes with high stack height and longitudinally placed stiffening element (ADV) was investigated in a pool of 32 recreational runners. After comparing ADV and CON against running in heavier familiar shoes (OWN), percentages of the participant pool benefitting at different magnitudes of metabolic saving were derived. When comparing percentages of participants benefitting from CON and ADV between visits, retest correlation coefficients were respectively 0.95 and 0.99. Across magnitudes, the typical errors of percentages benefitting were 9.18% (CON) and 3.46% (ADV). Stated group averages of i.e. 4% metabolic savings when running in ADV, may potentially lead to the false assumption that the stated benefit applies to every runner. In contrast, based on our introduced approach, one can reliably state that a metabolic saving of i.e. 4% can be expected for at least 25% of recreational runners. Therefore, the expected percentage population benefitting at given magnitudes might be a more transparent expression for developers, marketing teams and consumers considering the relatively large measurement error of footwear induced metabolic savings on individual level.